2017
DOI: 10.1186/s12913-017-2658-5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring health systems strength and its impact: experiences from the African Health Initiative

Kenneth Sherr,
Quinhas Fernandes,
Almamy M. Kanté
et al.

Abstract: BackgroundHealth systems are essential platforms for accessible, quality health services, and population health improvements. Global health initiatives have dramatically increased health resources; however, funding to strengthen health systems has not increased commensurately, partially due to concerns about health system complexity and evidence gaps demonstrating health outcome improvements. In 2009, the African Health Initiative of the Doris Duke Charitable Foundation began supporting Population Health Imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Yet, none of these studies were among primary care patients; two were among HIV + patients attending regional treatment centers, one was among university students, and one was among patients at a large specialized referral hospital. Moreover, using cut-off scores of 10 there was very high variability in sensitivity (27-91%), specificity (77-99%), diagnostic odds ratio (6)(7)(8)(9)(10), and area under the receiver operating characteristic curve (AUROC); (0.68-1). An additional validation study of the PHQ-9 from South Africa showed that a cut-off of 9 achieved a sensitivity of 49% and specificity of 94%, with a diagnostic odds ratio of 14 and AUROC of 0.85 (20).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, none of these studies were among primary care patients; two were among HIV + patients attending regional treatment centers, one was among university students, and one was among patients at a large specialized referral hospital. Moreover, using cut-off scores of 10 there was very high variability in sensitivity (27-91%), specificity (77-99%), diagnostic odds ratio (6)(7)(8)(9)(10), and area under the receiver operating characteristic curve (AUROC); (0.68-1). An additional validation study of the PHQ-9 from South Africa showed that a cut-off of 9 achieved a sensitivity of 49% and specificity of 94%, with a diagnostic odds ratio of 14 and AUROC of 0.85 (20).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of quantitative indicators or data for governance, leadership, and management, we utilized an approach combining qualitative data analyzed with a focus on codes related to the WHO's definition with a national document review to assess these factors. Other studies have employed similar approaches, in addition to developing quantitative measures that ask key informants to rate governance and leadership in the systems they work in [36][37][38]. The importance of health governance and leadership is a recurring theme in global health that impacts MNCH care across health system levels, and one which requires novel approaches to measurement and intervention to accelerate SDG progress [39].…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…For existing indicators to support policy and programme decision-making, they have to be valid, relevant and feasible in the new context for which they are intended [18][19][20]. To expand on the preliminary study that identified the indicators, in this study we aim to explore experts' perspectives on key issues that arise in reorienting indicators to monitor the continuum of care.…”
Section: Introductionmentioning
confidence: 99%